(untitled) (Research, Society and Development, 2021)
Breastfeeding is an important period of protection for the child. In the current global pandemic scenario of Covid-19, there are few researches carried out on pregnant women and their newborns, but it is known that the risk of transmission exists and should be taken into account in the act of breastfeeding. For this reason, this review presents as a guiding question: what is the evidence in the literature regarding breastfeeding in the context of Covid-19? This research is characterized as an Integrative Literature Review. The literature search took place in March/April 2021 and initially identified 171 articles. After reading 22 abstracts, 16 articles were selected and read in full. After the analytical reading of these articles, 10 articles were selected as the object of study for presenting aspects that answered the guiding question of this review. Through the analysis of the articles presented, it can be seen that the pandemic affected the practice of health care in the most diverse segments, bringing to light the need for adaptations in the conduct to be taken in view of the health demands of individuals. Through this integrative literature review, it was possible to find the main current recommendations regarding breastfeeding in the context of the Covid-19 pandemic. The main findings in this research corroborate the recommendations of national and international health entities regarding the practice of breastfeeding.